2017
DOI: 10.1016/j.alcohol.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine synthesis in alcohol drinking-prone and -resistant mouse strains

Abstract: Alcoholism is a prevalent and debilitating neuropsychiatric disease, and much effort has been aimed at elucidating the neurobiological mechanisms underlying maladaptive alcohol drinking in an effort to design rational treatment strategies. In preclinical literature, the use of inbred mouse lines has allowed for the examination of ethanol effects across vulnerable and resistant phenotypes. C57BL/6J mice consistently show higher rates of ethanol drinking compared to most mouse strains. Conversely, DBA/2J mice di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Molecule quantities were either taken from prior striatal models (Oliveira et al ., ; Kim et al ., ) or experimental publications or adjusted to reproduce experimentally measured concentrations of downstream molecules; for example, the balance of adenylyl cyclase and phosphodiesterase was adjusted to produce a 30 n m basal cAMP concentration (Bacskai et al ., ; Mironov et al ., ). Changes in molecule quantity due to chronic alcohol treatment were based on published experiments showing increase in Gβγ (Bowers et al ., ), increase in metabotropic glutamate receptor types 1/5 (mGluR1/5) (Obara et al ., ; Meinhardt et al ., ), lower evoked dopamine (Hirth et al ., ; Siciliano et al ., ), changes in Gs‐coupled signaling (Lucchi et al ., ; May et al ., ; Nestby et al ., ; Kashem et al ., ), or increased calcium influx due to increases in NMDA receptor 2B (NR2B) subunits relative to NR2A subunits (Wang et al ., ; Chen et al ., ; Ma et al ., ). Initial conditions specifying molecule quantities are available on github (https://github.com/neurord/D1pathways/blob/master/IC_SPNspineAChm4R_AC1_coupleGqhigh.xml).…”
Section: Methodsmentioning
confidence: 99%
“…Molecule quantities were either taken from prior striatal models (Oliveira et al ., ; Kim et al ., ) or experimental publications or adjusted to reproduce experimentally measured concentrations of downstream molecules; for example, the balance of adenylyl cyclase and phosphodiesterase was adjusted to produce a 30 n m basal cAMP concentration (Bacskai et al ., ; Mironov et al ., ). Changes in molecule quantity due to chronic alcohol treatment were based on published experiments showing increase in Gβγ (Bowers et al ., ), increase in metabotropic glutamate receptor types 1/5 (mGluR1/5) (Obara et al ., ; Meinhardt et al ., ), lower evoked dopamine (Hirth et al ., ; Siciliano et al ., ), changes in Gs‐coupled signaling (Lucchi et al ., ; May et al ., ; Nestby et al ., ; Kashem et al ., ), or increased calcium influx due to increases in NMDA receptor 2B (NR2B) subunits relative to NR2A subunits (Wang et al ., ; Chen et al ., ; Ma et al ., ). Initial conditions specifying molecule quantities are available on github (https://github.com/neurord/D1pathways/blob/master/IC_SPNspineAChm4R_AC1_coupleGqhigh.xml).…”
Section: Methodsmentioning
confidence: 99%
“…Given that alcohol intoxication results in reduced performance in a variety of tasks (Hendrie, Gao, Hall, Hui, & Unverzagt, 1996;Starkey & Charlton, 2014;Van Dyke & Filmore, 2014) and its potential to influence dopaminergic reward systems (Siciliano et al, 2017), it is not surprising that a number of studies have sought to investigate its effects on the medial frontal system via its impact on the aforementioned ERP components (Henry, 2013;Nelson, Collins, Lang, & Bernat, 2011, Ridderinkhof, Cohen, & Forstmann, 2012. Nelson et al (2011) found that intoxication impaired the performance of the aforementioned medial-frontal error evaluation system.…”
Section: Introductionmentioning
confidence: 99%
“…These effects result initially in everincreasing tolerance, withdrawal and continued drug seeking, while, withdrawal from opiates and alcohol, for example, can also lead to a hyperdopaminergic state (44). Chronic use of these substances including cocaine also induces a hypodopaminergic state © 1996-2017 leading to tolerance (45)(46)(47). Specifically, Siciliano et al, (46) found that there was an attenuation of baseline dopamine synthesis in the ventral striatum after two cycles of chronic intermittent ethanol (CIE).…”
Section: Substance Use Disorder (Sud) and Rds: A Biological Bi-directmentioning
confidence: 99%
“…Chronic use of these substances including cocaine also induces a hypodopaminergic state © 1996-2017 leading to tolerance (45)(46)(47). Specifically, Siciliano et al, (46) found that there was an attenuation of baseline dopamine synthesis in the ventral striatum after two cycles of chronic intermittent ethanol (CIE). They also found that low dopaminergic activity was positively correlated with drinking as indicated by high dopamine/metabolite ratios.…”
Section: Substance Use Disorder (Sud) and Rds: A Biological Bi-directmentioning
confidence: 99%